Practice of Participatory Budgeting at the Corporate Foundation - Yahyu Indiarti; Wiwit Adityani; Antonius Jatmiko; Nurita Affan; Hariman Bone; Wulan I R Sari (Journal of International Conference Proceedings (JICP), 2022)
Budget participation in the organization is intended to have a positive effect on control and motivation in achieving goals and public accountability. However, budget participation also sometimes does not work well due to several obstacles, such as miscommunication, lack of commitment, and low motivation to perform. Foundation as a non-profit oriented organization has a unique situation in terms of performance. Performance that is identical to profit oriented applied to non-profit organization certainly has its own phenomenon. Whether a corporate foundation performing better than foundation in general by implementing a participatory budgeting is very interesting to explore. The purpose of this study is to explore the implementation and evaluation of participatory budgeting, particularly in the education sector, at foundation owned by company. This research approach is qualitative with case study on a Company Foundation K. The company foundation is the unit of analysis of this research. The informants involved were teachers, company staff from the Business and Support Division, the Education Office, and staff of foundation from the Education Division. The results of the study indicate that the success of implementation participatory budgeting is influenced by internal schools, such as principals and teachers and external schools, such as regulations from the company and the Education Office/government. The biggest challenge is the inconsistency in the implementation that is different from the planning. Changes in policies and changes in implementation procedures, both internally and externally, affect the staff’s motivation and responsibility for implementing the budget. Thus, the performance of budget absorption, especially at the education sector, has not been optimal can be improved by developing participatory budgeting practices that are transparent, participatory, and accountable. Keywords: Participatory Budget Implementation, Participatory Budget Evaluation, Corporate Foundation, Non-Profit Oriented, Budget Performance.